Acute Monoarthritis of the Wrist Joint: Tuberculosis or Not? - Desikan, Prabha; Verma, Rahul; Tiwari, Karuna; Panwalkar, Nikita (Journal of Wrist Surgery, 2016)
Background Extrapulmonary tuberculosis (EPTB) is known to have many and varied presentations. However, isolated involvement of bone with tubercular infection is uncommon. The clinical features of such infections are known to mimic chronic pyogenic osteomyelitis, Brodie abscess, or tumors, but not acute monoarthritis. Case Description We describe here an unusual case of tuberculous osteomyelitis that mimicked features of acute monoarthritis of the wrist joint. Literature Review Extraspinal tuberculous osteomyelitis is rare and comprises only about 2 to 3% of all cases of osteoarticular tuberculosis, with the hip and knee joints being the most commonly involved. An extensive literature review did not show any published report of tuberculous osteomyelitis presenting as acute monoarthritis of the wrist joint. Clinical Relevance This case underlines the importance of making EPTB an important differential diagnosis even in cases with clinical features that are completely inconsistent with tubercular infections.
Keywords: monoarthritis; wrist; tuberculosis